Cognitive explorations into metaphor and metonymy - Polzenhagen, Frank; Kövecses, Zoltán; Vogelbacher, Stefanie; Kleinke, Sonja (Peter Lang Edition, 2014)
This volume presents selected contributions to an annual symposium on metaphor and metonymy held at the English Department of Heidelberg University. It brings together papers by lecturers, PhD students and graduates from three universities - Heidelberg University, Eoetvoes Lorand University in Budapest, and the University of East Anglia in Norwich. The contributions illustrate the plurality of perspectives and methods in current cognitive-linguistic research on metaphor and metonymy and exemplify some of the ways in which they can be combined. The papers also attest to the wide range of domain
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2012 -- Heidelberg; Psycholinguistik; Kognitive Linguistik; Metonymie; Metapher